Evolution of the Islamic Education Teacher Performance Measurement System Based on Competence in the Digital Era: A Literature Review - Sasmita, Jumiati; Haryati, Laily; Pirdaus, Sukri; Hanif, Fauzan (International Journal of Islamic Thought and Humanities, 2025)
This study examines the evolution of competency-based Islamic Religious Education (PAI) teacher performance measurement systems in the digital era. This study is a literature study aimed at digging up data and information on new topics or issues. The goal is to formulate more accurate questions that will be answered in further research or later research. The type of data used is secondary data. The data collection method is a literature study. The results of the study state that in an effort to improve the quality of public services, the government needs to utilize various online platforms such as websites, mobile applications, and social media. Performance measurement is a management of performance achievement. Continuous performance measurement will provide feedback, so that continuous improvement efforts will achieve success in the future. Islamic Religious Education (PAI) teachers as human resources working in educational institutions are always assessed by their superiors. The performance measurement system in the world of education, especially for Islamic Religious Education (PAI) teachers, has undergone a long evolution so that the use of digitalization is not only in performance measurement but also in the process of implementing education that leads to the success of a teacher's performance.